2016
DOI: 10.1111/brv.12261
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and genetic connectivity: the role and consequences of reproduction, dispersal and recruitment in seagrasses

Abstract: Accurate estimation of connectivity among populations is fundamental for determining the drivers of population resilience, genetic diversity, adaptation and speciation. However the separation and quantification of contemporary versus historical connectivity remains a major challenge. This review focuses on marine angiosperms, seagrasses, that are fundamental to the health and productivity of temperate and tropical coastal marine environments globally. Our objective is to understand better the role of sexual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 182 publications
3
74
0
Order By: Relevance
“…Studies examining both sexual and asexual reproduction have found that while some seagrass populations rely largely on clonal growth for population maintenance (Rasheed, , ), in the case of large scale meadow loss (Rasheed, McKenna, Carter, & Coles, ), or for annual or ephemeral populations (Hovey et al., ; York et al., ), sexual reproduction is of critical importance. Seagrass fruits and propagules of most species are capable of dispersing long distances via the convective forces of ocean waves and currents (Kendrick et al., ; McMahon et al., ). Long distance dispersal supports meadow connectivity and the natural recolonisation of sites after disturbance events (Kendrick et al., ); however, very few studies have attempted to quantify seagrass dispersal and connectivity at broad spatial scales (Jahnke et al., ; Ruiz‐Montoya, Lowe, & Kendrick, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examining both sexual and asexual reproduction have found that while some seagrass populations rely largely on clonal growth for population maintenance (Rasheed, , ), in the case of large scale meadow loss (Rasheed, McKenna, Carter, & Coles, ), or for annual or ephemeral populations (Hovey et al., ; York et al., ), sexual reproduction is of critical importance. Seagrass fruits and propagules of most species are capable of dispersing long distances via the convective forces of ocean waves and currents (Kendrick et al., ; McMahon et al., ). Long distance dispersal supports meadow connectivity and the natural recolonisation of sites after disturbance events (Kendrick et al., ); however, very few studies have attempted to quantify seagrass dispersal and connectivity at broad spatial scales (Jahnke et al., ; Ruiz‐Montoya, Lowe, & Kendrick, ).…”
Section: Introductionmentioning
confidence: 99%
“…Seagrass fruits and propagules of most species are capable of dispersing long distances via the convective forces of ocean waves and currents (Kendrick et al., ; McMahon et al., ). Long distance dispersal supports meadow connectivity and the natural recolonisation of sites after disturbance events (Kendrick et al., ); however, very few studies have attempted to quantify seagrass dispersal and connectivity at broad spatial scales (Jahnke et al., ; Ruiz‐Montoya, Lowe, & Kendrick, ). Tropical seagrasses occur in some of the world's most threatened coastal regions (Orth et al., ; Waycott et al., ), and there is a critical need to assess the role of connectivity in seagrass replenishment and recovery after disturbance events, the effect of disturbance events on seagrass connectivity and its implications for the conservation of coastal habitats (York et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because of the historical paradigm that sexual reproduction contributes only marginally to the maintenance and growth of populations. However, there is growing recognition that the long-term persistence of species depends to some extent on sexual reproduction, as even low rates of recruitment may provide evolutionary potential and increased resistance/resilience to environmental alterations (Reusch et al, 2005; Ehlers et al, 2008; Reynolds et al, 2012; Kendrick et al, 2016). Recruitment by seed also plays a role in colonizing new habitats or recolonizing following local extinction, and contributes to patch expansion in some species (Orth et al, 2006; van Dijk et al, 2009; Kendrick et al, 2012; McMahon et al, 2014; Furman et al, 2015; Sherman et al, 2016; Smith et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Distinguishing the historical effects of gene migration and vicariance on contemporary genetic structure is problematic without testable biogeographical hypotheses based on pre‐existing geological and environmental evidence (Nason et al ., ). A capacity for long‐distance dispersal (LDD) and demographic connectivity over multiple climatic epochs is a feature in the movement ecology of seagrasses, with significant evolutionary and ecological consequences associated with the different life‐history stages (Kendrick et al ., , ). The effective dispersal of sexually derived propagules by water plays an important role in range expansion into new habitats, range shifts under changing environmental conditions, and population turnover (Triest, ; Johnson et al ., ).…”
Section: Introductionmentioning
confidence: 99%